Implementation of "the consensus statement for the standard of care in spinal muscular atrophy" when applied to infants with severe type 1 SMA in the UK. Issue 10 (8th October 2009) - Roper, H; Quinlivan, R
Abstract : The diagnosis of severe type 1 spinal muscular atrophy (SMA) should be confirmed by an expert in paediatric neuromuscular disease. Invasive investigations are not usually necessary as the diagnosis is confirmed with a DNA blood test. Care thereafter should be delivered close to home by a multidisciplinary team with a clear point of access during times of crisis. The aim of care is to keep the infant as well as possible with the best possible quality of life. There are many forms of active respiratory management which can help maintain the well-being of infants with severe type 1 SMA. These include approaches to reduce the risk of infection and aspiration and appropriate techniques of airway and secretion clearance. The use of non-invasive ventilation may be helpful for some, usually less-severely affected infants, particularly to assist extubation. Long-term invasive ventilation is not recommended. Active assessment of feeding and nutrition is vital, and most babies can be managed well with nasogastric feeds. Gastrostomy may be considered for some infants, but the benefits should be carefully weighed against the risks. It is vital to share information and formulate an anticipatory care plan with the infant's parents from the point of diagnosis.